Oleuropein and Antibacterial Activities of Olea europaea L. Leaf Extract - S. Himour; A. Yahia; H. Belattar (European Scientific Journal, ESJ, 2017)
In this study, we reported the determination of phenolic compounds in olive leaves by reversed phase HPLC/DAD and the evaluation of their in vitro activity against several microorganisms. These organisms might however, be causal agents of human intestinal and respiratory tract infections. Extract of the leaves of two varieties of Olea europaea L. (Chemlel and Dathier) was investigated for antibacterial activity against four pathogenic bacteria. Leaves extract was prepared using water and methanol (20/80) in a cold extraction process. The tested bacteria were Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Staphylococcus aureus .The extracts were found to be effective against all isolates tests. Ethanolic extract at a concentration of 100 % presented the highest potential of inhibiting variety of Dathier against S.aureus .This is with an inhibition zone of 17.49 mm and 15.66 mm for the variety Chemlel against S.aureus. The high Oleuropein content and the important antibacterial activities of olive leaves extract could be useful sources for industrial extraction and pharmacological application.